Actual areas of improvement of Ukrainian legislation in the field of prevention of gender-based violence - Prus, Ihor (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article analyzes current directions of improvement of the legislative institute in the field of prevention of gender-based violence in Ukraine. Information about a positive trend in regulatory changes to the Criminal Code of Ukraine and the Code of Ukraine on Administrative Offenses was studied. t was found that the term «gender-based violence» includes not only women and girls, but also other population groups, as well as different situations in which such a manifestation of violence is possible. The opinion is proved that the legislation itself or the appropriate changes made to it will not be able to fully provide a mechanism for combating gender-based violence. The importance of the interaction of regulatory provisions and practical actions of relevant state authorities, local self-government bodies, public organizations, and medical services in the mechanism of combating gender-based violence is highlighted. At the same time, it was found that the National Police of Ukraine plays a significant role in ensuring an effective response system to violence. The problem of repeated perpetration of such violence, impunity for the offender, and generally «healthy» social relations directly depends on the effectiveness of the response of the authorized units of the National Police of Ukraine to the facts of violence and counteraction to it. Attention is paid to the issue of a particular aggravation of gender-based violence during the period of Russia’s armed aggression. The «weakness» of the norms of international law regarding the prosecution of perpetrators of violent acts was determined. Conclusions were made that the adoption of a number of legal acts on the regulation of gender relations led to the formation of a mechanism for realizing gender equality, reducing cases of discrimination, ensuring equal rights of women and men in all spheres of society’s life.